STRC Deletion is a Frequent Cause of Slight to Moderate Congenital Hearing Impairment in the Czech Republic - Plevova, Pavlina; Paprskarova, Martina; Tvrda, Petra; Turska, Petra; Slavkovsky, Rastislav; Mrazkova, Eva (Otology & neurotology, 2017)
OBJECTIVE: This study aimed to clarify the molecular epidemiology of hearing loss by identifying the responsible genes in patients without GJB2 mutations. STUDY DESIGN: Prospective genetic study. SETTING: Tertiary referral hospital. PATIENTS: Fifty one patients with bilateral sensorineural hearing loss, 20 men, and 31 women, mean age 24.9 years, range 3 to 64 years, from 49 families. GJB2 and deltaGJB6-D13S1830 mutations were excluded previously. INTERVENTION: Diagnostic. Sixty-nine genes reported to be causative of hearing loss were analyzed. Sequence capture technology, next-generation sequencing, and multiplex ligation-dependent probe amplification (MLPA) were used. Coverage of STRC was screened in Integrative Genomics Viewer software. MAIN OUTCOME MEASURE: Identification of causal pathogenic mutations in genes related to deafness. RESULTS: Five families (10%) had recessive STRC deletions or mutations. Five unrelated patients (10%) had recessive mutations in TMPRSS3, USH2A, PCDH15, LOXHD1, and MYO15A. Three families (6%) had autosomal dominant mutations in MYO6A, KCNQ4, and SIX1. One family (2%) had an X-linked POU3F4 mutation. Thus, we identified the cause of hearing loss in 28% of the families studied. CONCLUSIONS: Following GJB2, STRC was the second most frequently mutated gene in patients from the Czech Republic with hearing loss. To decrease the cost of testing, we recommend STRC deletion screening with MLPA before next-generation sequencing. The existence of a pseudogene and polymorphic STRC regions can lead to false-positive or false-negative results when copy number variation analysis is based on next-generation sequencing data.
Keywords: mutace; dospělí; Female; dítě; předškolní dítě; Hearing Loss, Sensorineural; Adult; mladý dospělý; ženské pohlaví; Adolescent; lidé; membránové proteiny; Mutation; prospektivní studie; Male; Prospective Studies; Czech Republic; Child, Preschool; Young Adult; Membrane Proteins; Česká republika; lidé středního věku; Child; mužské pohlaví; percepční nedoslýchavost; Middle Aged; mladiství; Humans